Architects' data. - Neufert, Ernst, 1900-1986; Neufert, Peter, 1925-1999 (Oxford : Blackwell Science, 2000)
Architects' Data provides an essential reference for the initial design and planning of a building project. Organised largely by building type, and with over 6000 diagrams, it provides a mass of data on spatial requirements and also covers planning criteria and considerations of function and siting. Most illustrations are dimensioned and each building type includes plans, sections, site layouts and design details. There are substantial new sections on: · building components · services · heating · lighting · thermal and sound insulation · fire protection · designing for the disabled Drafting guidelines; Measurement basis; Design; Construction management; Building components; Heating and ventilation; Thermal and sound insulation; Fire protection and means of escape; Lightning protection/aerials; Artificial lighting and daylight; Windows and doors; Stairs, escalators and lifts; Refurbishment, maintenance and change of use; Roads and streets; Gardens; Houses and residential buildings; Educational and research facilities; Office buildings; Arcades; Retail outlets; Workshops and industrial buildings; Agricultural buildings; Public transport; Designing for vehicles; Airports; Fire stations; Restaurants; Hotels/Motels; Zoos and aquariums; Theatres/Cinemas; Sport and recreation; Healthcare buildings; Places of worship; Cemeteries and crematoria; Bibliography; Related standards; Conversion tables; Index
Keywords: Bouwkunde; Bouwplanning